Impact of Covid-19 on Sectors of Indian Economy and Business Survival Strategies - Dr. Debdas Rakshit; Ananya Paul (International Journal of Engineering and Management Research, 2020)
The entire world is in the clutch of Coronavirus. The dissemination of the virus is so colossal that it compelled the World Health Organisation (WHO) to declare it as pandemic. The outbreak of the virus has unprecedented implications on the global economy. Severe economic burden and grave consequences have to be borne by the Indian industries in this backdrop of declining economic situation due to coronavirus. Thus, this article is intended to study the repercussions of coronavirus on different sectors of Indian economy and to highlight the reasons for which India can be benefitted in the post pandemic period and mainly to specify the business survival strategies which is the key to overcome this tough situation.